Subacute infective endocarditis due to Lodderomyces elongisporus: a case report and review of the literature - Ye Qiu; Yongying Shi; Ying Mai; Zhile Wu; Jing Guan; Juanni Huang; Danhong Su; Feng Ye; Zhengtu Li (Frontiers Media S.A., 2023)
Lodderomyces elongisporus, a rare emerging pathogen, can cause fungemia often related to immunosuppression or intravenous devices. Herein, we report the case of a 58-year-old woman with subacute infective endocarditis due to Lodderomyces elongisporus identified by blood fungal culture and whole-genome sequencing, who was treated with antifungals, mitral replacement and endocardial vegetation removal surgery.